Principles for Effective Insolvency and Creditor/Debtor Regimes, 2021 Edition - World Bank (World Bank, Washington, DC, 2021)
Effective creditor and debtor rights and insolvency systems are an important element of financial system stability. The World Bank Group accordingly has been working with partner organizations to develop principles for insolvency and creditor and debtor rights systems. The principles for effective insolvency and creditor and debtor regimes are a distillation of international best practice on design aspects of these systems, emphasizing contextual, integrated solutions and the policy choices involved in developing those solutions. The principles have been designed as a broad-spectrum assessment tool to assist countries in their efforts to evaluate and improve core aspects of their commercial law systems that are fundamental to a sound investment climate, and to promote commerce and economic growth. Efficient, reliable, and transparent creditor and debtor regimes and insolvency systems are of key importance for the reallocation of productive resources in the corporate sector, for investor confidence, and for forward-looking corporate restructuring.